Knowledge regarding the prevention of chronic kidney disease in hypertensive and diabetic patients: a cross-sectional study - Elaine Cristina Santa Cruz de Moura; Jefferson Belarmino Nunes Barbosa; Patrícia Érika de Melo Marinho
Abstract Introduction: Hypertension (HT) and diabetes mellitus (DM) lead to functional and structural changes in target organs such as the kidneys, characterizing the need for preventive actions to avoid Chronic Kidney Disease (CKD). Objective: To verify cardiologists' and endocrinologists' knowledge, indications and practices regarding prevention of CKD in patients with HT and DM. Methods: A cross-sectional study with 14 cardiologists and 5 endocrinologists applying a questionnaire about the conduct of these professionals regarding the prevention of CKD in hypertensive and diabetic patients. Results: One hundred percent of the cardiologists and endocrinologists did not request specific tests for CKD screening (albuminuria and glomerular filtration rate (GFR), although 92.9% of the cardiologists and 60.0% of the endocrinologists report referring hypertensive and diabetic patients with impaired renal function to nephrologists. One hundred percent of the interviewees recognize the importance of physical exercise for their patients; however, only 68.6% of cardiologists and 60% of endocrinologists indicated a physiotherapist and/or physical trainer to implement these exercises. Conclusion: The professionals evaluated in this study do not request microalbuminuria and GFR examinations for hypertensive and diabetic patients as a follow-up routine, despite having found cases of renal function impairment in these patients; in contrast to what is proposed in the guidelines for hypertension and diabetes mellitus. They recognize the importance of physical exercise and report indicating their patients to a physiotherapist and/or physical trainer. We suggest continuing the study in order to ascertain the reasons for their not complying with the respective guidelines.